Periodic Plasmonic Nanoantennas in a Piecewise Homogeneous Background - Siadat Mousavi, Saba (Université d'Ottawa / University of Ottawa, 2012)
Optical nanoantennas have raised much interest during the past decade for their vast potential in photonics applications. This thesis investigates the response of periodic arrays of nanomonopoles and nanodipoles on a silicon substrate, covered by water, to variations of antenna dimensions. These arrays are illuminated by a plane wave source located inside the silicon substrate. Modal analysis was performed and the mode in the nanoantennas was identified. By characterizing the properties of this mode certain response behaviours of the system were explained. Expressions are offered to predict approximately the resonant length of nanomonopoles and nanodipoles, by accounting for the fringing fields at the antenna ends and the effects of the gap in dipoles. These expressions enable one to predict the resonant length of nanomonopoles within 20% and nanodipoles within 10% error, which significantly facilitates the design of such antennas for specific applications.
Keywords: Plasmonic nanoantenna; nanoantenna; nanomonopole; nanodipole; optical antenna